Frank Sinatra och de narrativa fälten - Klinkmann, Sven-Erik (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
The article argues for an understanding of popular icons such as Frank Sinatra as best seen through the concept of moving narrative fields, adopted from a theory of literary modes, put forward by Robert Scholes. The positive and negative poles of an icon such as Sinatra corresponds to the metaphor of glow and pain, used by Daniel Herwitz to describe the status of popular icons in general. In Sinatra’s case, as the article makes clear, a highly complex representation emerges, consisting of both mimetic and imaginary elements. The Sinatra icon is understood as a representation of coolness, romance and loneliness. Stereotypes associated with Sinatra are above all the romantic and swinging crooner/seducer and the loner/saloon singer. The narratives used in connection to Sinatra involve e.g. the film genre of film noir, but also other fictional genres such as the fairy tale, the soap opera, the Bildungsroman, the melodrama and the allegory. Besides an analysis of the narratives concerning Sinatra characterized by the modal approach, questions of artefacts are also addressed, artefacts which do not easily fit into any given modal context. Such "floating" artefacts associated with the Sinatra icon, discussed in the text, are cigarettes, tobacco smoke, the Fedora hat and, briefly, the microphone. A critique is also offered of attempts to formulate a "totalizing", homogenous narrative of the Sinatra icon.